THE INFLUENCE OF COMPLAINT HANDLING, MARKETING COMMUNICATION AND TRUST ON LOYALTY (MARKETING MANAGEMENT LITERATURE REVIEW) - Sri Fitriya; Zefri Efdison; Edia Satria; Dori Hp Putra (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Literature review article on the influence of complaint handling, marketing communication and trust on customer loyalty of PT Bank BSI Sungai Penuhis a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) Complaint Handling affects Loyalty; 2) Marketing Communication influences Customer Loyalty; 3) Trust has an effect on Customer Loyalty; Customer. The research was carried out using quantitative methods, as well as a causal relationship research design. The research data is primary data collected through a questionnaire in the form of a google form, as well as secondary data collected by documentation techniques. Sampling was taken using a random sample, while the calculation technique used the Slovin formula so that a sample of 100 was obtained. However, only 75 respondents were willing to fill out the questionnaire. Data analysis technique using multiple regression analysis